Effects of magnesium and potassium supplementation on insomnia and sleep hormones in patients with diabetes mellitus - Khalid, Sidra; Bashir, Shahid; Mehboob, Riffat; Anwar, Tehreem; Ali, Muhammad; Hashim, Mariam; Waseem, Humaira; Basharat, Shahnai (Frontiers in Endocrinology, 2024)
It was a Randomized Controlled Trial (Single blind) study conducted at Diabetes Center of Akhuwat Health Services, Lahore, after taking institutional approval from The University of Lahore, Lahore, Pakistan. The research can contribute to the development of more effective treatment strategies. The findings of this research provides deeper insight into the relationship between insomnia and micronutrient deficiency and help reduce the burden of this disease on society. Therefore, the article's content aligns with the scope of International Journal of Public Health, which aims to publish original and high-quality research in public health.I confirm that this work is original and has not been published elsewhere, nor is it currently under consideration for publication elsewhere. All authors meet the Uniform Requirements for Manuscripts Submitted to Biomedical Journals criteria for authorship. We have no conflicts of interest to disclose. The similarity index of this article is 14%.